2012
DOI: 10.1007/s13744-012-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Species Richness and Host Specificity among Caterpillar Ensembles on Shrubs in the Andes of Southern Ecuador

Abstract: Caterpillar ensembles were sampled on 16 species of shrubs from the family Asteraceae and the genus Piper (Piperaceae) in open and forest habitats in the Andean montane forest zone of southern Ecuador between August 2007 and May 2009. Trophic affiliations of caterpillars to the host plants were confirmed in feeding trials. Overall, species richness of herbivorous caterpillars was high (191 species across all plants), but varied strongly between ensembles associated with different plant species (2-96 lepidopter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…Further circumstantial evidence suggests that herbivore densities might have been higher before the drought. Bodner et al (2012;personal communication) recorded considerably higher caterpillar abundance and species richness on three species of Asteraceae shrubs growing on successional habitat similar to our pasture sites in the Rio San Francisco area. Similarly, Plath et al (2012) reported higher diversity of arboreal Coleoptera for a 2-yearold, low-land timber plantations that was notably similar to the present design in species selection (i.e.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Further circumstantial evidence suggests that herbivore densities might have been higher before the drought. Bodner et al (2012;personal communication) recorded considerably higher caterpillar abundance and species richness on three species of Asteraceae shrubs growing on successional habitat similar to our pasture sites in the Rio San Francisco area. Similarly, Plath et al (2012) reported higher diversity of arboreal Coleoptera for a 2-yearold, low-land timber plantations that was notably similar to the present design in species selection (i.e.…”
Section: Discussionsupporting
confidence: 68%
“…Sample treelets were not uniform with regard to leaf area and larger treelets may conceivably have harbored more individuals, thereby potentially biasing the slope of the curves. Following Bodner et al (2012), we therefore re-scaled the x-axis of each accumulation curve by multiplying the original sample count with the average leaf area of a sample treelet belonging to that respective group. In addition to habitat and host-species level richness estimates provided by the species accumulation curves above, we used generalized linear models (GLM) to compare treelet-level a-diversities across tree species and habitat types for each of the four insect groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detritivorous caterpillars are not restricted to the leaf litter layer, but may also occur above‐ground on herbaceous or woody plants, where they feed on dead plant biomass (Bodner et al ., ). Epiphyll grazing caterpillars scrape algae, mosses, and lichens from leaves (Moskowitz & Westphal, ; Bodner et al ., , ). Even though non‐herbivorous feeding associations have been described in many caterpillar species, genera, or more inclusive groups, their role in ecosystems has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, their most commonly acknowledged function is herbivory, because their abundance levels may be high among the external chewers of some plants (Bodner et al 2012). On the other hand, they may be also extremely important as prey for insectivorous organisms (Matthews & González 2004;Marconato et al 2008).…”
mentioning
confidence: 99%